2006
DOI: 10.1128/jvi.02677-05
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Receptor Specificity and Cell Tropism in Mouse and Human Airway Epithelial Cells

Abstract: Recent human infections caused by the highly pathogenic avian influenza virus H5N1 strains emphasize an urgent need for assessment of factors that allow viral transmission, replication, and intra-airway spread. Important determinants for virus infection are epithelial cell receptors identified as glycans terminated by an ␣2,3-linked sialic acid (SA) that preferentially bind avian strains and glycans terminated by an ␣2,6-linked SA that bind human strains. The mouse is often used as a model for study of influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
324
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(358 citation statements)
references
References 59 publications
19
324
1
4
Order By: Relevance
“…MUC1 is expressed by virtually all of the surface columnar epithelial cells of the respiratory tract, as well as type II pneumocytes in the alveoli, 35 a major target of IAV infection. 29,36 During the normal cs-mucin recycling process in these cells, MUC1, MUC4 and MUC16 extracellular domains are shuttled to the cell surface in exosomes and upon release of the vesicle contents, will re-attach to the transmembrane domain via a SEA module, enabling continued and renewable expression of these glycoproteins at the cell surface. 37 Importantly, the content of exosomes obtained from bronchoepithelial samples have been demonstrated to have a neutralizing effect on human IAV.…”
Section: Discussionmentioning
confidence: 99%
“…MUC1 is expressed by virtually all of the surface columnar epithelial cells of the respiratory tract, as well as type II pneumocytes in the alveoli, 35 a major target of IAV infection. 29,36 During the normal cs-mucin recycling process in these cells, MUC1, MUC4 and MUC16 extracellular domains are shuttled to the cell surface in exosomes and upon release of the vesicle contents, will re-attach to the transmembrane domain via a SEA module, enabling continued and renewable expression of these glycoproteins at the cell surface. 37 Importantly, the content of exosomes obtained from bronchoepithelial samples have been demonstrated to have a neutralizing effect on human IAV.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza A virus primarily infects airway epithelial and antigen-presenting cells by binding to cell surface terminal oligosaccharides on sialic acid residues. Studies have shown that type II cells also express influenza virus receptors (17)(18)(19)(20). In fact, avian influenza H5N1 virus has also been detected in type II cells of humans who died during infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza A viruses primarily infect cells of the respiratory tract because of the selective binding of viral coat proteins to specific terminal oligosaccharides on sialic acid residues, which in humans and mice are typically found on airway epithelial cells, alveolar type II epithelial cells, and antigen-presenting cells (17)(18)(19)(20). It is generally considered that CD8 1 cytotoxic T lymphocytes (CTLs) are the principal means for viral clearance during a primary AT A GLANCE COMMENTARY Scientific Knowledge on the Subject Despite improved therapies for treating bronchopulmonary dysplasia (BPD), it is unknown why survivors are at increased risk for symptomatic respiratory infections and are often rehospitalized.…”
mentioning
confidence: 99%
“…It is noteworthy that mouse strain-dependent differences in the sialic acid composition have been reported [79]. Importantly, human and mouse airways differ in their pulmonary sialic acid repertoire [80,81] and the pneumococcus has evolved to specifically sense and respond to human sialic composition [82]. Therefore, the role of neuraminidases in human pneumonia is potentially underestimated by extrapolating from mouse models.…”
Section: Discussionmentioning
confidence: 99%